The use of multiple skills learned by the professional of modern languages to be focused in the business part of the hotel and tourism sector (2018)
The current final project of career consists on the elaboration for the creation and starting up of an academy of languages in Bogota’s city focused in hospitality and tourism. Since it is about a private academy of languages, we will begin placing it inside the sector of the educational services, and for it, we are going to differ between the legal and not legal formation, being the last the one that belongs to our company. Also we will elaborate a DOFA to synthesize the strong and weak points we’ve detected our academy has. Regarding to the operations’ plan, first the suitable place will be decided to establish the physical center where the activity is going to carried out, for which, we have to have in mind aspects like: the best zone to locate it and if there is availability for businesses which collect enough characteristics that fulfill what we are looking in a near future.